The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15177/seefor.18-13
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of Waste Wood Biomass as Biosorbent for the Removal of Synthetic Dye Methylene Blue from Aqueous Solutions

Abstract: Background and purpose: Wood and wood processing industries are generators of a substantial amount of waste wood biomass, such as wood chips, shavings and sawdust. Such waste is often unused and its disposal can be a serious environmental problem. Different lignocellulosic waste materials have been successfully used as low-cost adsorbents (biosorbents) for the removal of synthetic dyes, as well as other contaminants, from wastewater. The aim of this study was to valorise the waste wood biomass of ten tree spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…Furthermore, out of the tested samples, poplars are characterized by the smallest specific density and (thus) the highest internal porosity [26,27], which could be the reason for the highest biosorption efficiency. The same 10 biosorbents were screened for cationic dye Methylene Blue (MB) removal under similar experimental conditions (different contact time, t = 120 min) and showed exceptional biosorptive capability with over 90% MB removal in all runs [15]. These results are consistent with the research by Nacu [28] who reported that adsorption capacity of sawdust for cationic dyes is much higher than that for anionic dyes (such as CR).…”
Section: Screening Of Waste Biomass Of Different Wood Species As Biosorbents For Cr Removalsupporting
confidence: 83%
See 4 more Smart Citations
“…Furthermore, out of the tested samples, poplars are characterized by the smallest specific density and (thus) the highest internal porosity [26,27], which could be the reason for the highest biosorption efficiency. The same 10 biosorbents were screened for cationic dye Methylene Blue (MB) removal under similar experimental conditions (different contact time, t = 120 min) and showed exceptional biosorptive capability with over 90% MB removal in all runs [15]. These results are consistent with the research by Nacu [28] who reported that adsorption capacity of sawdust for cationic dyes is much higher than that for anionic dyes (such as CR).…”
Section: Screening Of Waste Biomass Of Different Wood Species As Biosorbents For Cr Removalsupporting
confidence: 83%
“…Pine bark 1.6 100 [9] Lemon-scented gum sawdust 0.523 >80 [10] Fir (Abies nordmanniana) sawdust 28.1 86 [11] Chir pine (Pinus roxburghii) sawdust 5.8 72 [12] Eucalyptus (Eucalyptus globulus) sawdust ->80 [13] Methylene Blue White cedar sawdust 55.15 - [14] Poplar waste biomass 21.9 98.50 [15] Pine sawdust (Pinus strobus) 10.3 99.94 [16] Cedar tree sawdust 142.36 - [17] Basic Violet 1 Chir pine (Pinus roxburghii) sawdust 11.3 96 [12] Disperse Orange 30 Poplar sawdust 0.089 83.4 [18] Eriochrome Black T Sawdust unspecified 40.96 80 [19] Allura Red AS Sawdust unspecified 50.98 - [20] Safranine O Sawdust unspecified -98 [21] Compared to activated carbon and biochar, native lignocellulosic materials as biosorbents are mostly inferior, i.e., adsorption capacities of native materials are lower. Therefore, attempts have been made to improve the adsorption capacities of such materials by phys-ical and/or chemical methods, including the production of biochar.…”
Section: Congo Redmentioning
confidence: 99%
See 3 more Smart Citations